Understanding tricuspid valve remodelling in atrial fibrillation using three-dimensional echocardiography. (5th May 2020) - Ortiz-Leon, Xochitl A; Posada-Martinez, Edith L; Trejo-Paredes, Maria C; Ivey-Miranda, Juan B; Pereira, Jason; Crandall, Ian; DaSilva, Paul; Bouman, Eileen; Brooks, Alyssa; Gerardi, Christine; Ugonabo, Ifeoma; Chen, Wanwen; et al.
Abstract: Aims: Atrial fibrillation (AF) has been associated with tricuspid annulus (TA) dilation in patients with severe functional tricuspid regurgitation (TR); however, the impact of AF is less clear in patients without severe TR. Our aim was to characterize TA remodelling in patients with AF in the absence of severe TR using 3D transoesophageal echocardiography (TOE). Methods and results: Ninety patients underwent clinically indicated transthoracic and TOE: non-structural (NS)-AF ( n = 30); AF with left heart disease (LHD) ( n = 30), and controls in sinus rhythm ( n = 30). Three-dimensional TOE datasets were analysed to measure TA dimensions using novel dedicated tricuspid valve software. The NS-AF group showed biatrial dilatation and normal right ventricular (RV) size with decreased longitudinal function compared to controls, whereas the LHD-AF group showed biatrial dilatation, RV enlargement, decreased biventricular function, and higher systolic pulmonary artery pressure compared with the other groups. Indexed TA area, minimum diameter, maximum diameter, and total perimeter were significantly larger in the NS-AF group than in controls (measurements in end-diastole: 6.4 ± 1.1 vs. 5.0 ± 0.6 cm 2 /m 2, 1.8 ± 0.3 vs. 1.6 ± 0.2 cm/m 2, 2.1 ± 0.3 vs. 1.9 ± 0.2 cm/m 2, and 6.6 ± 0.9 vs. 5.9 ± 0.7 cm/m 2, respectively, all P < 0.05). There was no significant difference in any indexed TA parameter between AF groups. TA circularity index (ratio between minimum and maximal diameters) and TA fractional area change between end-diastole and end-systole were no different among the three groups. Conclusion: AF is associated with right atrial and tricuspid annular remodelling independent of the presence of LHD in patients with intrinsically normal tricuspid leaflets without severe TR.